Complications and their management following retroperitoneal lymph node dissection in conjunction with retroperitoneal laparoscopic radical nephroureterectomy. (10th February 2022) - Kanno, Toru; Kobori, Go; Ito, Katsuhiro; Nakagawa, Hiromichi; Takahashi, Toshifumi; Takaoka, Naoto; Somiya, Shinya; Nagahama, Kanji; Ito, Masaaki; Megumi, Yuzuru; Higashi, Yoshihito; Moroi, Seiji; et al.
Abstract : Objectives: To describe the detailed perioperative complications and their management after retroperitoneal lymph node dissection with retroperitoneal laparoscopic radical nephroureterectomy for patients with upper tract urothelial carcinoma at three institutions. Methods: Retroperitoneal lymph node dissection was performed on patients with upper tract urothelial carcinoma located at the pelvis and/or upper or middle ureter, and its template included the renal hilar and para‐aortic lymph nodes (left side) and the renal hilar, paracaval, retrocaval, and intra‐aortocaval lymph nodes (right side). The lymph nodes and kidneys were removed en bloc. The primary endpoint was postoperative complication rates, and the secondary endpoints were intraoperative findings and chylous leakage management. The associations of retroperitoneal lymph node dissection with postoperative complications were examined using logistic regression with propensity score techniques. Results: Eighty‐eight (31%) and 195 (69%) patients underwent and did not undergo retroperitoneal lymph node dissection, respectively. There was no significant difference in postoperative complications and other perioperative findings in the entire cohort, except for prolonged operation time. Retroperitoneal lymph node dissection was not statistically significantly associated with total and serious complications in propensity score analyses. Postoperative chylous leakage could be conservatively managed even though it is common in patients with retroperitoneal lymph node dissection (14/88 (16%)). The incidence of chylous leakage was significantly lower in patients whose lymphatic vessels were meticulously clipped completely during retroperitoneal lymph node dissection (5.3% vs 24%; P = 0.017). Conclusion: There was no association between retroperitoneal lymph node dissection with laparoscopic radical nephroureterectomy and postoperative complications. However, chylous leakage is often observed after retroperitoneal lymph node dissection and careful management is highly required. The use of clips during retroperitoneal lymph node dissection is recommended to minimize chylous leakage risk.